Spatial and temporal change characterization of Ceratium furcoides (Dinophyta) in the equatorial reservoir Riogrande II, Colombia (2012)
ABSTRACT: Aim: To establish the dynamics of C. furcoides in horizontal and temporal scales; and to determine the main ecological factors related to its dynamics. Methods: Samples were taken in five stations between July 2002 and July 2003. Physical and chemical variables were sampled monthly. Density was evaluated by sampling carried out within the photic zone. Growth rate (r), Turnover rate (T), Generation Time (gt), Niche Width (NW), Taylor’s Power Law, and the rate of population change (σs ), were used. Canonical Correspondence Analysis (CCA) was used too. Results: Total density was 264163.4 cel.L–1, the highest was found in Up Río Chico and the lowest in Dam. The species was more clustered in space than in time. r ranged between 0.29 and 0.3 cel.d–1, gt between 1.8 and 2.4 days, T between 0.55 and 0.42 divisions per day, NW between 0.58 and 0.72, and σs between 0.3 d–1 and 2.3 d–1. The first three components of CCA explained 92.2% of the variation. Density was positively associated with chlorophyll a, NH4 + , RWCS and wind direction. Light attenuation, NO3 – , SiO2 and O2 were negatively associated with C. furcoides. Discussion: C. furcoides is a S strategist; it increases its density in the warmest periods under eutrophic conditions, low light penetration and high thermal stability; it is independent of the temperature but dependent of changes in rainfall and nutrients, – especially nitrogen – and not soluble phosphorus. Up Río Chico presented the best conditions for the increase of C. furcoides, since this station presented the highest levels of total nitrogen, and the highest relative stability. Conclusion: C. furcoides has a very similar ecology to that of C. hirundinella. It is an organism highly variable in temporal and spatial scales, with a wide niche and a clustered distribution. It belongs to the Morpho-funtional Group V and to Lo and LM Assotiations.